LEIA Discovery of the Longest-lasting and Most Energetic Stellar X-Ray Flare Ever Detected - Mao, Xuan; Liu, He-Yang; Wang, Song; Ling, Zhixing; Yuan, Weimin; Cheng, Huaqing; Pan, Haiwu; Li, Dongyue; Favata, Fabio; Ji, Tuo; Zhang, Jujia; Zhao, Xinlin; et al. (The Astrophysical journal, 2025)
The Lobster Eye Imager for Astronomy (LEIA) detected a new X-ray transient on 2022 November 7, identified as a superflare event occurring on a nearby K-type giant star HD 251108. The flux increase was also detected in follow-up observations at X-ray, UV, and optical wavelengths. The flare lasted for about 40 days in soft X-ray observations, reaching a peak luminosity of ∼1.1 × 10 34 erg s −1 in 0.5–4.0 keV, which is roughly 60 times the quiescent luminosity. Optical brightening was observed for only one night. The X-ray light curve is well described by a double fast rise and exponential decay model, attributed to the cooling process of a loop arcade structure formed subsequent to the initial large loop with a half-length of ∼1.9 × 10 12 cm. Time-resolved X-ray spectra were fitted by a four-temperature apec model (with three components being the quiescent background), showing significant evolution of plasma temperature and emission measure over time. The estimated energy released in the LEIA band is ∼3 × 10 39 erg, suggesting that this is likely the most energetic X-ray stellar flare with the longest duration detected to date.